Bridging Scales in Alzheimer's Disease: Biological Framework for Brain Simulation With The Virtual Brain - Stefanovski, Leon; Meier, Jil Mona; Pai, Roopa Kalsank; Triebkorn, Paul; Lett, Tristram; Martin, Leon; Bülau, Konstantin; Hofmann-Apitius, Martin; Solodkin, Ana; McIntosh, Anthony Randal; Ritter, Petra (Frontiers in Neuroinformatics, 2021)
Despite the acceleration of knowledge and data accumulation in neuroscience over the last years, the highly prevalent neurodegenerative disease of AD remains a growing problem. Alzheimer's Disease (AD) is the most common cause of dementia and represents the most prevalent neurodegenerative disease. For AD, disease-modifying treatments are presently lacking, and the understanding of disease mechanisms continues to be incomplete. In the present review, we discuss candidate contributing factors leading to AD, and evaluate novel computational brain simulation methods to further disentangle their potential roles. We first present an overview of existing computational models for AD that aim to provide a mechanistic understanding of the disease. Next, we outline the potential to link molecular aspects of neurodegeneration in AD with large-scale brain network modeling using The Virtual Brain (www.thevirtualbrain.org), an open-source, multiscale, whole-brain simulation neuroinformatics platform. Finally, we discuss how this methodological approach may contribute to the understanding, improved diagnostics, and treatment optimization of AD.